2013
DOI: 10.3390/molecules18067058
|View full text |Cite
|
Sign up to set email alerts
|

The Skin Secretion of the Amphibian Phyllomedusa nordestina: A Source of Antimicrobial and Antiprotozoal Peptides

Abstract: Antimicrobial peptides (AMPs) from the dermaseptin and phylloseptin families were isolated from the skin secretion of Phyllomedusa nordestina, a recently described amphibian species from Northeastern Brazil. One dermaseptin and three phylloseptins were chosen for solid phase peptide synthesis. The antiprotozoal and antimicrobial activities of the synthetic peptides were determined, as well as their cytotoxicity in mouse peritoneal cells. AMPs are being considered as frameworks for the development of novel drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…Even though the arsenal of bioactive peptides in the skin of each amphibian species is generally different, the identification of the same bioactive peptide in more than one amphibian species was previously reported. Namely, the case of the antimicrobial peptide dermaseptin 01 [48] originally identified in P. oreades, that was afterwards also identified in other three species in same genus: P. azurea, P. nordestina, and P. hypochondrialis [49,50].I n this work, we report the peptide antioxidin-I that was present in three genera of tropical amphibians. These observations evidence that antioxidin-I potentially performs an important and an efficient physiological role contributing to maintenance of frog's homeostasis.…”
Section: Purification and Structural Characterization Of Antioxidinmentioning
confidence: 67%
See 1 more Smart Citation
“…Even though the arsenal of bioactive peptides in the skin of each amphibian species is generally different, the identification of the same bioactive peptide in more than one amphibian species was previously reported. Namely, the case of the antimicrobial peptide dermaseptin 01 [48] originally identified in P. oreades, that was afterwards also identified in other three species in same genus: P. azurea, P. nordestina, and P. hypochondrialis [49,50].I n this work, we report the peptide antioxidin-I that was present in three genera of tropical amphibians. These observations evidence that antioxidin-I potentially performs an important and an efficient physiological role contributing to maintenance of frog's homeostasis.…”
Section: Purification and Structural Characterization Of Antioxidinmentioning
confidence: 67%
“…The evaluation of the cytotoxicity of peptides isolated from amphibian skin in normal cells is relevant and important to determine the biocompatibility. Brand and co-workers [50] demonstrated that peptides isolated from the skin secretion of Phyllomedusa nordestina had no toxicity against mouse peritoneal macrophages. Additionally, low hemolytic and cytotoxic activity were detected in human erythrocytes and in the murine fibroblasts cell line NIH3T3, after 60 h exposure to peptides isolated from the skin secretion of the frog Leptodactylus pustulatus [59].…”
Section: Antioxidin Effects On Fibroblast Viability and Redox Balancementioning
confidence: 99%
“…Similar to human skin, amphibian skin exhibits a well‐developed chemical defence system by secreting antimicrobial peptides with a wide range of pharmacological activities (Brand et al . ). These peptides are synthesized and stored in the granular glands and are released when required, usually in response to a stressor, such as a predatory attack or an infection (Amiche et al .…”
Section: Introductionmentioning
confidence: 97%
“…Dermaseptins, a large family of antimicrobial amphipathic peptides (AMP) effective against bacteria, yeasts, fungi, protozoa and viruses, are part of host defence mechanisms against pathogens . Similar to human skin, amphibian skin exhibits a well-developed chemical defence system by secreting antimicrobial peptides with a wide range of pharmacological activities (Brand et al 2013). These peptides are synthesized and stored in the granular glands and are released when required, usually in response to a stressor, such as a predatory attack or an infection (Amiche et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding antiparasitic activity of AMPs, only 83 of more than 990 active peptides derived from amphibians registered at APD have been tested as antiparasitic, mostly having been tested for antimalaria activity . Furthermore, no correlation between antibacterial and antiparasitic activity potencies was observed in those AMPs that have been tested . Antimicrobial peptides have potential to form a new class of molecules able to treat neglected diseases, including those caused by parasites .…”
Section: Introductionmentioning
confidence: 99%